(untitled) (Journal of Hama University, 2024)
This research aims to study the effect of Buserelin injection in the twelfth day after insemination on the reproductive efficiency of Syrian Awassi sheep. The research was carried out on female Awassi sheep at the Hama Research Center of the General Commission for Scientific Agricultural Research. (14) animal was used in the experiment, with an average age of (3-5) years, and an average weight of 44 ± 2 kg. The experimental animals were examined and made sure that they were free from reproductive problems (ovaries - uterus - vagina). The females were randomly distributed into two groups: the first group (the experiment group) consisting of 7 animals, where vaginal sponges were placed for them on the first day, and after 14 days these sponges were withdrawn and the animals were injected With the pregnant mare serum gonadotropin (PMSG) in order to achieve estrus synchronization and stimulate follicular growth, and after 24 hours of injection of (PMSG), the ewes and rams were placed for insemination, and on the 12th day after insemination, these ewes were injected with a dose of 2 ml of Buserelin (GnRH analogue) in order to stabilize pregnancy. As for the second group (control), which consisted of 7 animals, it was treated according to the same previous program, with the replacement of Buserelin injections on the twelfth day after insemination with an injection of 2 ml of physiological saline. Pregnancy was diagnosed three months after conception in both groups by ultrasound. The results showed that there were no significant differences between the control group and the experimental group regarding the percentage of pregnant females, as all were pregnant, as well as the total birth rates. There were significant differences in the percentage of births in the control and experimental groups with regard to single births, as well as the rate of twinning. We conclude from the study that Buserelin injection on the twelfth day after insemination did not have a beneficial effect with regard to increasing the rates of pregnancy, births and twins under semi-intensive rearing conditions.